Pelaksanaan Asas Hukum Retroaktif Terhadap Penegakan Hukum Pidana Matrill - Triputra, Yuli Asmara; Rohman Hasyim (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Retroactive problems arise as a consequence of the application of the principle of legality. The principle of legality itself can be studied based on various aspects, such as historical aspects, socio-criminological aspects, aspects of legal reform in relation to imperative and linear views, aspects related to criminal politics and studies from our Weltanschaung perspective, namely Pancasila, a study of each aspect This gives different implications regarding the principle of legality which in the view of science the difference will actually enrich the repertoire of criminal law itself. The prohibition of retroactive application of a criminal regulation contained in Article 28 I paragraph (1) of the Second Amendment of the 1945 Constitution raises the implications of regulations under the 1945 Constitution cannot override this principle. The application of the Retroactive Principle is only related to material criminal law. From the sentences